Impact of Organizational Life Cycle Stages on Quality of Corporate Governance: Empirical Evidence from Pakistan’s Corporate Sector - Shaheen, Sundus; Nazir, Rabia; Mehar, Noreen; Adil, Fareeha (International Journal of Economics and Financial Issues, 2020)
The purpose of this research study is to determine the influence of the different organizational life cycle stages in modeling the quality of corporate governance. The study employs data of 46 companies listed with the KSE 100 index and uses a governance prediction model to determine the nexus between the organizational life cycle and the quality of corporate governance. The longitudinal data on corporate governance may help to identify the changes within a firm over time. However, of this time series data has compelled us to use the variations in corporate governance between-firms at distinct life-cycle stages. The study finds that mature firms as being high in resources are better governed overall. Transparency, responsibility, and accountability are higher in growth firms, whereas discipline and independence improve as firms mature. The results of the study recommend that governance functions such as monitoring/control and resource/strategy are significant and relatable at different life-cycle stages. Keywords: Corporate governance, organization life cycle, corporate sector, regression analysis, governance prediction model JEL Classifications G0, G3, G34 DOI: https://doi.org/10.32479/ijefi.10279